Certain Types of Weakly Closed Function - I. M. Ali, Radhi; Hussein AL-Bayati, Jalal H. (Iraqi Journal of Science, 2023)
The purpose of this paper is to give the condition under which every weakly closedfunction is closed and to give the condition under which the concepts of weaklysemiclosed function and weakly pre-closed function are equivalent. Moreover,characterizations and properties of weakly semi closed functions and weakly preclosedfunction was given.